Nutrition in Nepal : A National Development Priority - World Bank (World Bank, Washington, DC, 2017)
Malnutrition results from different combinations of immediate, underlying, and basic determinants. Inadequate dietary intake and disease are the immediate determinants of undernutrition. Underlying the immediate causes of undernutrition are three areas: (1) food security, (2) health services and health environment, and (3) care for women and children. Education is also critical. At the base of the framework are a host of interrelated causes including resources, economic structure, political and ideological structure, and formal and informal institutions.